Role of Green Supply Chain Management in embolden Competitiveness and Performance: Evidence from Indonesian Organizations - Armalia Reny Wijayanti Ananda; Pudji Astuty; Yudhinanto Cahyo Nugroho (International Journal of Supply Chain Management, 2018)
The current research investigates the empirical debate that impact of green supply chain management on competitiveness and performance. For doing this purpose, the current study divided performance into three sub-categories which are environmental performance, economic performance, and operational performance. The current study is conducted in the manufacturing industry in Indonesia. The results of structural equation modeling confirm that green purchasing, green information system, and eco-design have a positive and significant impact on competitiveness. Moreover, the results further suggested that competitiveness has also positively and significantly impact on environmental performance, economic performance and operational performance. The results further suggested that competitiveness is highly positive and significant impact on environmental performance followed by operational performance and economic performance. Therefore, it is recommended that competitiveness is the main factor in order to enhance and strengthen environmental and operational performance.